Is it Necessary to Send the Sleeve Gastrectomy Specimens to Pathology? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Background: Laparoscopic sleeve gastrectomy (LSG) has become more popular among other bariatric procedures. The histopathologic changes in the sleeve gastrectomy specimens have not been widely investigated among the Turkish population. Objective: The purpose of this study was to delineate these histopathologic findings of the LSG specimens of morbidly obese patients from a single center. Materials and Methods: A prospective database of all patients who have undergone LSG at a single center was reviewed. Demographic parameters, that is, sex, age, and body mass index were examined. The incidence of Helicobacter pylori, and other pathologic findings in the specimens were studied. Results: In total, 253 patients who had undergone LSG between the period spanning from April 2012 to January 2017 were included in the study. The 183 patients were female individuals and 70 patients were male individuals. The mean age at the time of operation was 38.5 years (range, 18 to 65 y). The mean body mass index was 47.7 kg/m(2). The pathologic findings were H. pylori positivity in 69 patients (27%), chronic active gastritis in 52 patients (20.5%), chronic gastritis in 135 patients (53.4%), and intestinal metaplasia in 5 patients (2%), whereas normal histopathologic findings were observed in 65 patients (25.7%). As regards surgical complications, the mortality rate was 0%, the staple-line leak was observed in 2 patients (0.8%), and intra-abdominal hemorrhage occurred in 2 patients (0.8%). Conclusions: The majority of patients who underwent LSG had pathologic findings in the resected specimens. With regard to the high incidence of pathologic findings in this study, we conclude that it is essential to send the gastrectomy materials for pathologic investigation after sleeve gastrectomy.
Keywords: Obesity; laparoscopic sleeve gastrectomy; pathologic findings; GASTRIC HISTOPATHOLOGIES; HELICOBACTER-PYLORI; OVERWEIGHT; OBESITY